Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru PAUD - Maya Kusumaningrum; Ghufron Abdullah; Noor Miyono (Universitas Muria Kudus, 2022)
This study aims to determine the effect of the principal's leadership style on the performance of PAUD teachers in Jambu District, Semarang Regency. The population in this study were all PAUD teachers in Jambu District, Semarang Regency with a total of 134 PAUD teachers. The sample was determined using the proportional random sampling technique using the formula from Slovin and then the sample in this study was 100 PAUD teachers. The data analysis used was descriptive analysis, prerequisite test, single regression analysis and multiple regression analysis which were processed using IBM SPSS Statistic 23. The results showed that there was a positive and significant effect of the principal's leadership style on the performance of PAUD teachers in Jambu District, Semarang Regency. This is evidenced by the magnitude of the value of R square is 0.621 = 62.1%, meaning that the magnitude of the influence of the X1 variable on Y is 62% and the magnitude of other influences outside of leadership styles that affect the performance of kindergarten teachers in Jambu District, Semarang Regency is 37, 9 % . Based on the results of these studies, it can be concluded that leadership style has a significant effect on PAUD teacher performance